SIMULATION IN NURSING EDUCATION: A LITERATURE REVIEW - Canute, Raymond James (Acta Scientiae et Intellectus, 2024)
The use of simulation is not a novel concept in nursing education. As early as the first two decades of 20th century, the educational preparation of future nurses has involved simulation-based experiences. Current practice in health care and nursing promotes the incorporation of evidence to guide professional decisions and practice. A review of literature and studies is undertaken to explore simulation in nursing education, as well as examine the available evidence to support its continued use as a pedagogical modality or tool in undergraduate nursing programs.